Automated aerial compression based on nonlinear multiple scale expansion - Шутко, В. М.; Колганова, О. О.; Ковтонюк, І. Ю.; Савченко, О. В. (Problems of Informatization and Control, 2013)
Paper develops automated aerial compression method based on nonlinear multiple scale expansion and opened its advantages over the Wavelet Analysis